Electrostatic hazards - Luttgens, Gunter; Wilson, Norman (Oxford ; Boston : Butterworth Heinemann, 1997)
This book provides a guide to the dangers of static electricity and how to avoid them. It is aimed at safety managers and professionals, as well as all personnel involved in the activities concerned in the chemical, agricultural, pharmaceutical, and petrochemical process industries.
Introduction; Danger of Fire and Explosion; Origins of Static Electricity; Principles of Safety Measures; Electrostatic Gas Discharges as an Ignition Source; Case Histories Related to Brush Discharges; Case Histories Related to Cone Discharges; Case Histories Related to Propagating Brush Discharges; Case Histories Relating to Spark Discharges -- Dusts, Hybrid Mixtures, Liquids; Case Histories Not Related to Electrostatics; Nuisances and Shock for Personnel; Index.
Includes bibliographical references and index.
Keywords: Industrial buildings -- Fires and fire prevention; Electrostatics; Industrial accidents -- Case studies; Electronic books; Case studies